Taguchi based self-configure data rate optimization AODVUU routing parameters in MANET over optical network performances - Khang, Adam Wong Yoon; Jamil Alsayaydeh, Jamil Abedalrahim; Indra, Win Adiyansyah; Pusppanathan, Jaysuman; Elias, Shamsul Jamel (Blue Eyes Intelligence Engineering And Sciences Publication, 2019)
Research and development advancements in the area of wireless technologies give rises of mobile ad hoc networks (MANET) domain but is constrained to the single networks and stand alone. Furthermore, the communication networking applications requirements mostly still depends on fixed infrastructure networks that lead to MANET need to communicate with internet. Consequently, the traditional mobile routing protocols proposed for MANET are inefficient but play an equivalent important role in the performances of mobile wireless network over optical backhaul with focusing of MANET of the wireless domain in access network. Routing protocols procedures are controlled with a set of parameters from being dragged to undesired situations such as un-optimized Quality of Service (QoS) resource consumption. These parameters have a direct impact on the efficiency of a routing protocol and the overall MANET network performances. This paper proposed an offline optimization through simulation design of experiment of the AODV-UU parameters of MANET is evaluated by performing Taguchi signal to noise ratio (SNR) method for fine-tuning the AODV-UU routing parameters using the OMNeT++ software. The work is further extended with self-configure multiple data rates (SCMDR) scheme-a cross-layer-specific technique. AODV-UU with Taguchi tuned under the proposed SCMDR scheme is compared with AODV-UU configuration of oRiG scheme also as respects to previous work is examined based on capacity consumption, end-to-end delay metric and energy consumption metric under the varying speed scenario. The obtained results showed that, AODV-UU with Taguchi configuration outperformed the AODV-UU for the mention performance metrics here. The existing of current access network of the telco operators can benefit from the proposed improvement here.